Pengaruh Senam Prolanis terhadap Kadar Glukosa Darah pada Penderita DM Tipe 2 di Puskesmas Pakuan Aji Lampung Timur 2021 - Aini, Nur Indah; Agustriyani, Feri (Ners Akademika, 2022)
Purpose: The aim of this study was to identify the effect of prolanic exercise on reducing blood sugar levels in type 2 diabetes mellitus sufferers at Pakuan Aji Public Health Center, East Lampung 2021. Research Methodology: This type of research is a quantitative, analytical research design with a pre-experimental one group pretest-postest approach. This research has been conducted at UPT Puskesmas Pakuan Aji East Lampung 2021. The sample required in this study is 39 respondents. The test used wilcoxon. Result: The results of the research on the effect of prolanic exercise on reducing blood sugar levels in patients with type 2 diabetes, obtained a p-value of 0.001. (p <0.05).